Improved plantain production - Ngo-Samnick, E. Lionelle (Technical Centre for Agricultural and Rural Cooperation, 2011)
An adaptable and ecological food source, plantain production can benefit enormously from a number of new production techniques. This practical, well-illustrated guide provides a step-by-step description of the main stages of producing plantain from stem fragments (PIF). An ideal resource for farmers and extension workers, it includes a description of the recommended steps for growing plantain, along with information about sales, control of pests and diseases, plantain use and recipes.